The state of health in the European Union (EU-27) in 2019: a systematic analysis for the Global Burden of Disease study 2019 - Santos, João Vasco; Padron-Monedero, Alicia; Bikbov, Boris; Grad, Diana Alecsandra; Plass, Dietrich; Mechili, Enkeleint A.; Gazzelloni, Federica; Fischer, Florian; Sulo, Gerhard; Ngwa, Che Henry; Noguer-Zambrano, Isabel; Peñalvo, José L.; et al. (BMC public health, 2024)
The European Union (EU) faces many health-related challenges. Burden of diseases information and the resulting trends over time are essential for health planning. This paper reports estimates of disease burden in the EU and individual 27 EU countries in 2019, and compares them with those in 2010. We used the Global Burden of Disease 2019 study estimates and 95% uncertainty intervals for the whole EU and each country to evaluate age-standardised death, years of life lost (YLLs), years lived with disability (YLDs) and disability-adjusted life years (DALYs) rates for Level 2 causes, as well as life expectancy and healthy life expectancy (HALE). In 2019, the age-standardised death and DALY rates in the EU were 465.8 deaths and 20,251.0 DALYs per 100,000 inhabitants, respectively. Between 2010 and 2019, there were significant decreases in age-standardised death and YLL rates across EU countries. However, YLD rates remained mainly unchanged. The largest decreases in age-standardised DALY rates were observed for “HIV/AIDS and sexually transmitted diseases” and “transport injuries” (each -19%). “Diabetes and kidney diseases” showed a significant increase for age-standardised DALY rates across the EU (3.5%). In addition, “mental disorders” showed an increasing age-standardised YLL rate (14.5%). There was a clear trend towards improvement in the overall health status of the EU but with differences between countries. EU health policymakers need to address the burden of diseases, paying specific attention to causes such as mental disorders. There are many opportunities for mutual learning among otherwise similar countries with different patterns of disease. • This article, systematically analysing GBD 2019 study estimates, presents an overview of the state of health in the European Union in 2019, compared to 2010. • There was an improvement in the overall health status of the EU, despite substantial differences between Member States. • Cardiovascular diseases and neoplasms are the major contributors to the overall burden of diseases in the EU in 2019. • The age-standardised rate of years lived with disability due to mental disorders has been increasing and is expected to increase even more because of the COVID-19 pandemic. • This report provides a framework upon which to base further region- and country-specific health policies and interventions, to support health planning and priority setting.
GBD 2019 EU State of Health Collaborators: Jost B. Jonas [und andere]
Gesehen am 27.02.2025